SviaB: Secure and verifiable multi‐instance iris remote authentication using blockchain - Mahesh Kumar Morampudi; Munaga V. N. K. Prasad; Surya Narayana Raju Undi (IET Biometrics)
Abstract Homomorphic encryption (HE) is the most widely explored research area in the construction of privacy‐preserving biometric authentication systems because of its advantages over cancellable biometrics and biometric cryptosystems. However, most of the existing privacy‐preserving biometric authentication systems using HE assume that the server performs computations honestly. In a malicious server setting, the server may return an arbitrary result to save computational resources, resulting in a false accept/reject. To address this, secure and verifiable multi‐instance iris authentication using blockchain (SviaB) is proposed. Paillier HE provides confidentiality for the iris templates in SviaB. The blockchain offers the integrity of the encrypted reference iris templates as well as the trust of the comparator result. The challenges of using blockchain in biometrics are also addressed in SviaB. Extensive experimental results on benchmark iris databases demonstrate that SviaB provides privacy to the iris templates with no loss of accuracy and trust in the comparator result.